Clonal Hematopoiesis From Next Generation Sequencing of Plasma From a Patient With Lung Adenocarcinoma: A Case Report - Ito, Munehiro; Fujiwara, Yutaka; Kubo, Takashi; Matsushita, Hiromichi; Kumamoto, Tadashi; Suzuki, Tatsuya; Sunami, Kuniko; Yamamoto, Noboru; Kohno, Takashi (Frontiers in Oncology, 2020)
Reliable and accurate next generation sequencing (NGS) technologies are important in precision medicine. Analysis using currently available NGS genomic tests is conducted on cancer-derived DNA collected from tumor tissue, blood, or both. Clonal hematopoiesis (CH) produces a detectable somatic clonal mutation that is commonly associated with clonal expansion of hematopoietic cells with age and genomic analysis of blood samples can be used to detect CH. A 74-year-old Korean male had lung adenocarcinoma with a metastasis to the left scapula. He underwent palliative radiotherapy to the left scapula and received multi-line chemotherapies. After disease progression, he underwent re-biopsy of the tumor tissue and concomitant blood sampling. NGS genomic testing revealed no significant genomic mutation in the tumor tissue DNA but showed the TP53 mutation C135Y in peripheral blood DNA. To investigate the discordance between the genotyping results in tumor tissue and blood, we tested for the TP53 mutation using a target sequencing test in blood and normal oral mucosa. The TP53 mutation C135Y was only detected in the blood sample, confirming the presence of TP53-mutated CH. Awareness of the strengths and weaknesses of each NGS genomic testing method is vital. Performing genomic testing on paired tumor and blood samples is effective for discriminating mutations derived from CH from germline mutations and somatic mutations in tumor cells.